1982
DOI: 10.1017/s0003356100000921
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of ensiled poultry litter

Abstract: Poultry litter collected from a commercial broiler house, bedded with wood shavings, was used. The material was screened and ground before it was ensiled either alone or with other agricultural by-products, namely chopped barley straw, a mixture of weeds and grapefruit peels. The digestible organic matter in the dry matter value in vitro (0·39) for litter was comparable with that for straw and weeds. Of the total nitrogen (36·3 g/kg dry matter), 0·19 was ammonia-nitrogen and 0·77 protein-nitrogen. Digestible e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
2
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 7 publications
2
17
2
2
Order By: Relevance
“…Although the quality of tomato pomace varies amongst countries based on the processing method, tomato varieties, ripening stages, etc., the nutrient content of tomato pomace in our study was compatible with those reported by Mirzaei-Aghsaghali and Maheri-Sis (2008). We agree with Hadjipanayiotou (1994), who concluded that it can be a potential protein source in animal nutrition, and we verify the findings of Elliott et al (1981) who stated that tomato pomace silage is a good source of fibre.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the quality of tomato pomace varies amongst countries based on the processing method, tomato varieties, ripening stages, etc., the nutrient content of tomato pomace in our study was compatible with those reported by Mirzaei-Aghsaghali and Maheri-Sis (2008). We agree with Hadjipanayiotou (1994), who concluded that it can be a potential protein source in animal nutrition, and we verify the findings of Elliott et al (1981) who stated that tomato pomace silage is a good source of fibre.…”
Section: Discussionsupporting
confidence: 91%
“…Ensiled tomato pomace can be a potential protein-and energy source in animal nutrition (Hadjipanayiotou 1994). It is a good source of fibre (Elliott et al 1981), and it can be used as a substitute for good quality roughages (Omer and Abdel-Magid 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All wastelages had pleasant aroma, desirable yellowish green colour, soft texture and no mould growth was observed any of the wastelage, indicating optimum fermentation. A pleasing aroma and good colour were obtained when poultry litter was ensiled with forage maize (Harmon et al, 1975), citrus pulp or weeds (Hadjipanayiotou, 1982). The pH of wastelage was shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Most effective and easy solution of these problems is to use the excreta for feeding animals either by drying or ensiling with poor quality forages. Poultry wastes can be rendered free of pathogens by ensiling (Hadjipanayiotou, 1982;Daniels et al,. 1983) and deep stacking (Strickler, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being used for fattening, olive cake can also be used in the production of sheep, goat and cow milk (Hadjipanayiotou, 1999;Chiofalo et al, 2004). Research has proved (Hadjipanayiotou, 1994a) that ensilage can be safely used for prolonged storage of olive cake on its own, in combination with other by-products (molasses, poultry litter), or with conventional fodder (barley or maize grain).…”
mentioning
confidence: 99%